Die obere Hauensteinlinie Bahnbauten seit 1853 - Weidmann, Ruedi 1966- (Scheidegger & Spiess, 2009)
SCB.
Keywords: Maring, Rudolf Ludwig -- 1820-1893; Etzel, Carl -- 1812-1865; Geschichte; Eisenbahnbau; Alte Hauensteinlinie; Bildband